Simultaneous Analysis of Twelve Bile Acids by UPLC-MS and Exploration of the Processing Mechanism of Bile Arisaema by Fermentation - Qimiao Zhao; Guoshun Shan; Dan Xu; Hui Gao; Ji Shi; Chengguo Ju; Guimei Lin; Fan Zhang; Tianzhu Jia (Journal of Analytical Methods in Chemistry)
Ultrahigh-performance liquid chromatography (UPLC) coupled with quadrupole time-of-flight tandem mass spectrometry (Q/TOF-MS) in the MS/MS mode and UPLC coupled with triple quadrupole mass spectrometry (QqQ-MS) using the multiple reaction monitoring (MRM) mode were used to make a qualitative and quantitative analysis of twelve bile acids in Bile Arisaema. The fragmentation pathway of twelve bile acids was proposed. The quantification method showed a good linearity over a wide concentration range (R2 > 0.99), repeatability (RSD < 4.12%), stability (RSD < 4.25%), precision (RSD < 4.06%), and recovery (95.36–102.15%). Content of twelve compounds in Bile Arisaema varied significantly depending on region. Chemometric methods, hierarchical clustering analysis (HCA), and principal components analysis (PCA) were successfully used to optimize the fermentation time of the Bile Arisaema. The results suggested that the Bile Arisaema could complete fermentation in 15 days. The possible processing mechanism of Bile Arisaema promoted the transformation of conjugated bile acids into free bile acids in fermentation.